The Impact of Digitalization on Economic Growth in Developing Countries - Mirzatul Kadri; Wisnu Satria (Heca Sentra Analitika, 2026)
This study analyzes the impact of digitalization on economic growth in developing countries. In the modern era, digital technology has become a key driver of global economic transformation. Using panel data for 50 developing countries from 2010 to 2020, this study examines the relationship between digitalization and economic growth, measured by real gross domestic product (GDP) per capita growth. The indicators of digitalization include internet penetration, smartphone usage, and digital infrastructure, while education, foreign direct investment (FDI), and urbanization are included as control variables. The empirical analysis employs panel data regression using a Fixed Effects Model (FEM). The results indicate that digitalization makes a significant contribution to economic growth in developing countries. In particular, higher internet penetration, greater smartphone usage, and improved digital infrastructure are associated with enhanced productivity and efficiency across key economic sectors. In addition, education, FDI, and urbanization play important complementary roles by facilitating the adoption and effective use of digital technologies. These findings suggest that policymakers in developing countries should prioritize investment in digital infrastructure and expand digital access to maximize the growth benefits of digitalization.